Proses Penciptaan Komposisi Musik “PEDHOT” untuk Violin dan Piano karya Eki Satria - Eki Satria (Institut Agama Kristen Negeri Kupang, 2021)
This study aims to describe the process of composing music composition through empirical ideas. The author highlights an incident that is often encountered in a concert or string instrument recital, especially the violin, which is an incident in the form of breaking a string during a performance. From this observation, the author has the idea of ??composing a musical composition where the breaking of the strings becomes a conceptual part of a performance. The research method used is a qualitative method with a descriptive approach through three stages, namely literature study, observation and experimentation. In the process, the realization of the breaking of the strings in this composition is found at the end of the codetta as the closing of the work. Meanwhile, creative processing which is carried out based on the word